AJVR Reviewers, 2012 (American Journal of Veterinary Research, 2013)
Objective To evaluate the effects of metoclopramide and azithromycin on liquid-phase gastric emptying (GE) in a clonidine-induced delayed GE model using the acetaminophen absorption test (AAT). Methods This was a randomized crossover study of healthy, purpose-bred, mixed-breed dogs performed in a controlled laboratory setting from May through July 2023. Dogs received 1 of 4 treatments 1 hour before ingesting a liquid meal containing 25% of their resting energy requirement and 20 mg/kg acetaminophen: no treatment (control), clonidine (0.03 mg/kg, SC), clonidine plus azithromycin (4 mg/kg, IV), or clonidine plus metoclopramide (0.5 mg/kg, SC). Using high-power liquid chromatography, plasma acetaminophen concentrations were measured in 11 samples collected preprandially and at 10 time points between 0.5 and 24 hours postprandially. Time to peak concentration was used as a proxy for GE time. Results were analyzed by 2-way ANOVA with Sidak post hoc comparisons. Results 8 intact female dogs were included and received all 4 treatments in a random sequence. All dogs tolerated the AAT procedure well. Clonidine significantly delayed GE, increasing time to peak concentration from 80.6 ± 15.9 minutes to 187.5 ± 53.8 minutes. Neither metoclopramide nor azithromycin reversed this delay. Conclusions The AAT identified delayed liquid-phase GE following clonidine administration. However, at the investigated dosages, metoclopramide and azithromycin did not mitigate clonidine-induced delayed GE. Clinical relevance The AAT shows potential as a clinical tool for identifying delayed GE of liquids, particularly in critically ill or postoperative patients.